Indigenous peoples' rights and marine protected areas. (January 2018) - Ban, Natalie C.; Frid, Alejandro
Abstract: Marine protected areas (MPAs) are inherent to international commitments to protect the oceans and have the potential to recognize, honour, and re-invigorate Indigenous rights. Involvement of Indigenous peoples in the governance and management of MPAs, however, has received little attention. A review of the literature revealed only 15 publications on this topic (< 0.5% of papers on MPAs). In these case studies, governance arrangements of MPAs involving Indigenous peoples ranged from state-led to community-based, and included a spectrum of approaches in between. Cultural goals—which are compatible with biodiversity conservation—were emphasized by Indigenous peoples, and ecological goals were prevalent in state-led marine protected areas. Achievement of at least some cultural goals was the most common mention of success, whereas social issues were the most common challenge. Additional work is needed to ensure that existing and future MPAs serve the dual goals of biodiversity conservation and supporting Indigenous rights. Highlights: Marine protected areas are being established primarily to protect biodiversity. Indigenous peoples have inherent rights, including to marine resources. Marine protected areas have the potential to support Indigenous rights. Research on MPAs and Indigenous governance and management is limited. MPAs that involve Indigenous peoples achieve cultural conservation goals.